CNN Indonesia TV Broadcasting Media Business Strategy 2023 – 2025 - Arief Hakim; Aprihatiningrum Hidayati (School of Business, IPB University (SB-IPB), 2023)
Popular and high-value news programs on CNN Indonesia TV are essential for educating the audience and presenting the positive aspects of various situations. These programs play a significant role in the business unit's connection to the convergence strategy established by the Transmedia Group. This research aims to formulate a comprehensive business strategy for CNN Indonesia TV from 2023 to 2025, to achieve a competitive edge over other news television channels in Indonesia. The method employed for this study was a descriptive qualitative approach, which involved conducting interviews with professionals from CNN Indonesia. The interviews focused on various aspects, including business-related matters, contextual analysis, opportunities, and competitive conditions. The document study was utilized to explore information obtained from various sources within CNN Indonesia, including the company's business reports, operating systems, and operational processes. The strategic sharpening framework was employed, which entailed analyzing current business practices, identifying key elements of success, conducting a competitive profile analysis, performing a SWOT analysis, utilizing the TOWS Matrix, and creating the Internal-External Matrix. These steps were taken to derive future business strategy recommendations. The results of this study is CNN Indonesia TV should implement some business strategies, namely Continuous programming (PPT), Expansion of new audiences (PAB), and Optimization of current audiences (MAS). CNN Indonesia TV needs to enhance its viewership and advertising revenue by distinguishing itself from the competition and capitalizing on its ability to attract a significant share of the market. Therefore, it is imperative to formulate a corporate strategy that could adapt and anticipate changes in the competitive environment. Keywords: business strategy, cnn indonesia tv, media broadcasting, television, tows matrix